ANALYSIS OF SPEECH ACT IN BINTANG EMON’S VIDEO ON INSTAGRAM - Ammade, Salasiah; Rasyid, Asriadi; Marzuki, Zulfrida; Sahabuddin, Ilham (Faculty of Languages and Literature, Universitas Negeri Makassar, 2025)
This study investigates the use of speech acts in Bintang Emon’s videos on Instagram. The research aims to identify and analyse the types of speech acts—such as locutionary, illocutionary, and perlocutionary acts—used by the comedian to convey humour, critique, and social commentary. The data for this qualitative research were collected through content analysis of selected videos posted on Bintang Emon’s Instagram account. The findings reveal that Bintang Emon effectively uses a combination of assertive, directive, expressive, and commissive speech acts to engage his audience and deliver his messages in a humorous yet impactful manner. The findings show the analysis of speech act by Bintang Emon covers representative act, and instruction act, In the analysis of the video, the most frequent type of speech act that emerge is representative type act. The study concludes that understanding the speech acts in Bintang Emon’s videos can provide deeper insights into how humour and social critique are communicated in digital platforms, particularly in the context of contemporary Indonesian society.